Polarization transfer of Bremsstrahlung arising from spin-polarized electrons - Märtin, Renate; Surzhykov, Andrey; Winters, Danyal Ferdinant Alexander; Yerokhin, Vladimir (Physical review letters, 2012)
We report on a study of the polarization transfer between transversely polarized incident electrons and the emitted x rays for electron-atom bremsstrahlung. By means of Compton polarimetry we performed for the first time an energy-differential measurement of the complete properties of bremsstrahlung emission related to linear polarization, i.e., the degree of linear polarization as well as the orientation of the polarization axis. For the high-energy end of the bremsstrahlung continuum the experimental results for both observables show a high sensitivity on the initial electron spin polarization and prove that the polarization orientation is virtually independent of the photon energy.